2018
DOI: 10.1080/19490976.2018.1451276
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of pathogenic bacteria in the gut microbiota of infants at risk of developing celiac disease: The PROFICEL study

Abstract: Celiac disease (CD) is an immune-mediated enteropathy involving genetic and environmental factors, whose interaction influences disease risk. The intestinal microbiota, including viruses and bacteria, could play a role in the pathological process leading to gluten intolerance. In this study, we investigated the prevalence of pathogens in the intestinal microbiota of infants at familial risk of developing CD. We included 127 full-term newborns with at least one first-degree relative with CD. Infants were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 42 publications
2
64
0
3
Order By: Relevance
“…The fact that genetic susceptibility is not determinant for the presentation of CD (30–40% of the population have the required genotype but the prevalence of CD is only about 1%) has prompted research to discover what other factors can predict the clinical manifestation of the disease [ 21 ]. For example, there is enough evidence to suggest that the gut microbiota (especially Bacteria) plays a role in the onset and clinical manifestations of CD [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and probably other GRD. Although the exact mechanisms involved in the relationship of the gut microbiota and gut diseases are currently unknown (a relationship that is likely to be highly individualized as well), fellow colleagues have suggested an interesting proposal involving first a microbial dysbiosis (e.g., after antibiotic therapy), independent of gluten sensitivity, which then drives an activation of the innate immune system resulting in the secretion of pro-inflammatory molecules, epithelial barrier disruption, and an increased transfer of gluten peptides, a cascade that ultimately may lead to CD development [ 15 ].…”
Section: Grd and The Gut Microbiotamentioning
confidence: 99%
“…The fact that genetic susceptibility is not determinant for the presentation of CD (30–40% of the population have the required genotype but the prevalence of CD is only about 1%) has prompted research to discover what other factors can predict the clinical manifestation of the disease [ 21 ]. For example, there is enough evidence to suggest that the gut microbiota (especially Bacteria) plays a role in the onset and clinical manifestations of CD [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and probably other GRD. Although the exact mechanisms involved in the relationship of the gut microbiota and gut diseases are currently unknown (a relationship that is likely to be highly individualized as well), fellow colleagues have suggested an interesting proposal involving first a microbial dysbiosis (e.g., after antibiotic therapy), independent of gluten sensitivity, which then drives an activation of the innate immune system resulting in the secretion of pro-inflammatory molecules, epithelial barrier disruption, and an increased transfer of gluten peptides, a cascade that ultimately may lead to CD development [ 15 ].…”
Section: Grd and The Gut Microbiotamentioning
confidence: 99%
“…Various chronic disorders such as inflammatory bowel disease [13], and type 1 diabetes [14] have been shown to be associated with alterations in the gut microbial composition. Recent studies have also suggested that intestinal dysbiosis may play a role in the pathogenesis of coeliac disease [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…6 Animal studies have demonstrated that the postnatal period is an important phase for enteric host-microbe homeostasis, and early life perturbations of the gut microbiota by infection or antibiotic use could potentially lead to adverse gastrointestinal tract outcomes in humans later in life. 7,8 A meta-analysis found a positive association between antibiotic exposure and new-onset Crohn's disease; therefore, early infection or antibiotic use may also increase the risk of CD. 9 Several epidemiological studies have investigated the contributions of infection and antibiotic exposure to the risk of CD, reporting varying results.…”
Section: Introductionmentioning
confidence: 99%